2005
DOI: 10.1186/1471-2148-5-34
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Although there are now about 200 complete bacterial genomes in GenBank, deep bacterial phylogeny remains a difficult problem, due to confounding horizontal gene transfers and other phylogenetic "noise". Previous methods have relied primarily upon biological intuition or manual curation for choosing genomic sequences unlikely to be horizontally transferred, and have given inconsistent phylogenies with poor bootstrap confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…3). The resulting topology is in good agreement with rRNA trees [27], recently published concatenated-protein phylogenies [28,29], as well as supertree phylogenies [30]. In particular, we do recover the clade named "Terrabacteria" by Battistuzzi and co-workers, as well as the clade named Gracilicutes by Cavalier-Smith [7], separated with a high bootstrap support (BS 94%).…”
Section: Resultssupporting
confidence: 84%
“…3). The resulting topology is in good agreement with rRNA trees [27], recently published concatenated-protein phylogenies [28,29], as well as supertree phylogenies [30]. In particular, we do recover the clade named "Terrabacteria" by Battistuzzi and co-workers, as well as the clade named Gracilicutes by Cavalier-Smith [7], separated with a high bootstrap support (BS 94%).…”
Section: Resultssupporting
confidence: 84%
“…Among this set of marker genes, the COG0012 gene (a ribosome-associated GTPase) has a number of beneficial traits. In earlier studies, this COG was shown to be useful for inferring phylogenetic relationships with high fidelity, yielding results that are congruent with ribosomal RNA analyses (Harris, 2003; Bern and Goldberg, 2005; Mende et al, 2013). In addition to the phylogenetic resolution COG0012 provides, its features suggest it as a useful marker for defining relationships among closely related microbial taxa.…”
Section: Methodsmentioning
confidence: 58%
“…However, the novelty of this contribution is that by using the iterative bio-informatics approach, we can show that the WXG100 protein superfamily can be divided into three subfamilies: CFP-10-, ESAT-6- and sag EsxA-like. In addition, the phylogeny analysis of WXG proteins indicates that the Actinobacteria might be evolutionarily closer to the bacterial phylum Firmicutes than previously thought [27]. Subsequent analyses of the genetic organisation of WXG100 genes show that CFP-10- and ESAT-6-like genes are always encoded together on a bi -cistronic operon in contrast to the mono-cistronic s ag EsxA-like genes.…”
Section: Discussionmentioning
confidence: 91%